Establishment and Cooperation of Sino-Russian Arctic Think Tanks in Universities: Context, Positioning, and Pathways - Lv Peiying (Евразийская интеграция: экономика, право, политика, 2024)
In the context of the rapid development of science and technology and the complexity of the geopolitical landscape, the Arctic region has become a frontier of international competition. Russia and China, as important participants in Arctic affairs, not only share common interests in the fields of geopolitics and economics but also possess significant potential for cooperation in maintaining stability and sustainable development in the region. In recent years, scientific and technological diplomacy has become an important tool for interstate interaction, and the construction and cooperation of Arctic think tanks at universities in Russia and China are gradually transforming into a primary format for scientific and technological diplomacy.Aim. This article aims to explore the establishment of think tanks at universities in China and Russia in the field of Arctic research, analyze their role and positioning in scientific and technological diplomacy, and further investigate specific pathways for cooperation between universities, along with recommendations for optimizing interactions.Methods. Through a systematic review and empirical analysis, the cooperation and establishment of think tanks in universities in China and Russia concerning Arctic issues are examined.Results. The cooperative pathways of Arctic think tanks in Chinese and Russian universities include conducting joint scientific research and expeditions to achieve data and resource sharing; regularly holding international conferences and academic exchanges to facilitate political dialogue and knowledge transfer; utilizing research results from think tanks to provide policy recommendations to the government, supporting decision-making for both countries on Arctic issues. Additionally, cooperation among think tanks can enhance exchanges and collaborations in fields such as information technology and environmental protection, promoting joint development.Conclusions. The research findings indicate that cooperation between the think tanks of universities in China and Russia on Arctic issues effectively promotes interaction between the two countries in areas such as politics, information technology, resource utilization, and environmental protection, providing intellectual support for the Arctic strategies of both countries and playing an active role in global governance.